2022
DOI: 10.1007/s13105-022-00915-3
|View full text |Cite|
|
Sign up to set email alerts
|

Irisin improves adiposity and exercise tolerance in a rat model of postmenopausal obesity through enhancing adipo-myocyte thermogenesis

Abstract: The prevalence of obesity and its associated metabolic disorders, along with their healthcare costs, is rising exponentially. Irisin, an adipomyokine, may serve as a critical cross-organ messenger, linking skeletal muscle with adipose tissue and the liver to integrate the energy homeostasis under diet-induced obesity. We aimed to explore the putative role of irisin in the protection against obesity in a postmenopausal rat model by modulating energy expenditure (EE). Bilateral ovariectomy (OVX) was performed. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…Hence, it has been proposed that irisin modulates Sln, which can improve the function and thermogenesis of skeletal muscle. 42 In addition, in 2022, Son et al demonstrated in a mouse model of MO that the expression of sarcolipin and Ucp3 in skeletal muscle is decreased in offspring with diet-induced obesity and that this change is due to pathway regulation other than Find5/irisin. According to our results, we did not find that obesity by programming or Epi treatment modified the expression of Sln or Ucp3 in the offspring of 110 or 245 pnd; as mentioned for Fndc5/irisin or Pgc-1 α, the regulation of thermogenesis in skeletal muscle could occur through pathways other than Fndc5/irisin.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it has been proposed that irisin modulates Sln, which can improve the function and thermogenesis of skeletal muscle. 42 In addition, in 2022, Son et al demonstrated in a mouse model of MO that the expression of sarcolipin and Ucp3 in skeletal muscle is decreased in offspring with diet-induced obesity and that this change is due to pathway regulation other than Find5/irisin. According to our results, we did not find that obesity by programming or Epi treatment modified the expression of Sln or Ucp3 in the offspring of 110 or 245 pnd; as mentioned for Fndc5/irisin or Pgc-1 α, the regulation of thermogenesis in skeletal muscle could occur through pathways other than Fndc5/irisin.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that mice were prone to insulin resistance by globally deleted irisin via CRISPR/Cas-9 and high-fat-diet (HFD) ( Wang et al, 2023 ). In addition, the insulin resistance of HFD-treated bilateral ovariectomy rats was reduced by irisin therapy ( Gheit et al, 2022 ). However, chronic voluntary wheel running exercise ameliorates metabolic index in HFD-induced obese C57BL6J mice, while no difference was found in serum irisin ( Cho et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was associated with a decrease in the activity of gluconeogenic liver enzymes and restoration of liver glycogen content. Irisin reduces ectopic lipid inflation and increases energy expenditure by activating thermogenesis in muscle and adipose tissue and reducing metabolic efficiency [20].…”
Section: огляди літератури / Literature Reviewsmentioning
confidence: 99%